Revitalisasi Unit Tandon Air Bersih Bumdes Sebagai Upaya Peningkatan Kesejahteraan Masyarakat Desa Talungeng - Nabila Maylani Zahra; Selfi Puspitasari; Rosnia Rosnia; Muh. Kafsir Nawal; Rishan Rishan; Muhammad Ardi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The revitalization of the Village-Owned Enterprise (BUMDes) clean water reservoir unit represents a community empowerment strategy aimed at improving access to basic services while enhancing the welfare of rural communities. This program was implemented in Talungeng Village with a focus on upgrading water reservoir infrastructure, strengthening the capacity of BUMDes management, and increasing community participation in clean water service management. The program employed a participatory approach through several stages, including problem identification, program planning, revitalization implementation, socialization, and evaluation. The results indicate improvements in the quality and continuity of clean water distribution, enhanced effectiveness in managing the BUMDes clean water business unit, and increased community awareness regarding the sustainable use and maintenance of available facilities. The revitalization also generated social and economic benefits by reducing difficulties in accessing clean water, increasing community productivity, and strengthening public trust in BUMDes as a village economic institution. These findings demonstrate that strengthening clean water infrastructure integrated with community empowerment can serve as a sustainable rural development model oriented toward improving community welfare.